2019
DOI: 10.1051/0004-6361/201834506
|View full text |Cite
|
Sign up to set email alerts
|

Reclassification of Cepheids in the Gaia Data Release 2

Abstract: Context. Classical Cepheids are the most important primary indicators for the extragalactic distance scale. Establishing the precise zero points of their period-luminosity and period-Wesenheit (PL/PW) relations has profound consequences on the estimate of H 0 . Type II Cepheids are also important distance indicators and tracers of old stellar populations. Aims. The recent Data Release 2 (DR2) of the Gaia spacecraft includes photometry and parallaxes for thousands of classical and Type II Cepheids. We seek to r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
132
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(141 citation statements)
references
References 67 publications
9
132
0
Order By: Relevance
“…The coefficients of these relations at varying the ML relation and the efficiency of the superadiabatic convection, are reported in Table 11 and Table 12 for F and FO models, respectively. To derive the Wesenheit magnitude we adopt the relation provided by Ripepi et al (2019) < W >=< G > −1.9 < G BP − G RP >. Both the PLC and the PW relations hold for each individual pulsator thus allowing us to derive individual distances of observed Cepheids in the Gaia database.…”
Section: The Period-radius and The Period-mass-radius Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coefficients of these relations at varying the ML relation and the efficiency of the superadiabatic convection, are reported in Table 11 and Table 12 for F and FO models, respectively. To derive the Wesenheit magnitude we adopt the relation provided by Ripepi et al (2019) < W >=< G > −1.9 < G BP − G RP >. Both the PLC and the PW relations hold for each individual pulsator thus allowing us to derive individual distances of observed Cepheids in the Gaia database.…”
Section: The Period-radius and The Period-mass-radius Relationsmentioning
confidence: 99%
“…In this context, the Gaia mission (Gaia Collaboration et al 2016) is producing a 3D-map of 1 billion stars of the Milky Way with unprecedented accuracy. Focusing on pulsating stars, after the recent Data Release 2 (Gaia Collaboration et al 2018;Holl et al 2018), a large sample of Cepheids, observed in three photometric bands (G, G BP and G RP ) complemented with accurate parallaxes and proper motions, is available to the scientific community (Clementini et al 2019;Ripepi et al 2019), and the future releases will provide also radial velocity time series. This important database represents a challenging benchmark for testing the physical and numerical assumptions of current pulsation models.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the inner disk cepheids the A K s values from col. 3 in Table 3 in I19 based on the Cardelli et al (1989) reddening law were taken, converted to A V using A K s /A V = 0.114 and then converted to E(B − V) using a specific reddening of 3.1. The pulsation type listed in Col. 3 is from the independent classification by Ripepi et al (2019). The adopted distance (d) is listed in Col. 6 based on the reference in Col. 7.…”
Section: The Samplementioning
confidence: 99%
“…The analysis by Ripepi et al (2019) on the classification of CCs addresses one of the issues that also affected the analysis in G18. The classification as CCs was taken from the literature in that paper and the origin of this classification is sometimes hard to trace.…”
Section: Introductionmentioning
confidence: 99%
“…New streams, kinematic substructures and past accretion events have been found (Helmi et al, 2017;Koppelman et al, 2018), from the inner galaxy to the outer halo, and studies of dwarf galxies in the local group were carried out as well (Fritz et al, 2018). Various tracers were used to further explore the galaxtic structure, such as cepheids to trace the warp of the galactic disk (Ripepi et al, 2019).…”
Section: The Second Gaia Data Releasementioning
confidence: 99%